Treatment Strategies and Challenges in the Co-Management of Type 2 Diabetes and Tuberculosis - Vishwanath Ingle, Pravinkumar; Sivanandy, Palanisamy; Tse Yee, Wong; Siaw Ying, Wong; Kai Heng, Tee; Hang Chong, Tang; Zhi Xiang, Tan; Lean Tsu Ching, Wendy; Kit Mun, Toh (Journal of Pharmacy and Nutrition Sciences, 2022)
Despite rapid advances in the healthcare field, diabetes mellitus (DM) and tuberculosis (TB) continues to be a global burden that affects millions of people every year. The association between DM and TB has been known for an extended period. The last 15 years, however, have seen an increased number of studies showing that diabetes (both type 1 and type 2) increases the risk of tuberculosis because of impaired immune defences and likewise, TB may induce hyperglycemia and therefore increase the risk of DM. When DM and TB co-exist as dual diseases, it complicates management strategies as treatment outcomes are affected. In developing countries where the epidemic of DM and TB is rapidly growing, the presence of a concomitant disease becomes a challenge to the affected nation and could also impact DM and TB control on a global scale. This review brings together information on what is currently known about T2DM and TB as a double epidemic, the recommended treatment strategies, and the challenges involved in disease management. Furthermore, we address the future perspectives of the co-management of T2DM and TB and what can be done to overcome the shortcomings of currently available guidelines.